An immunodetection assay developed using cobra cytotoxin-specific antibodies: Potential diagnostics for cobra envenoming. (September 2022) - Ong, Hui Ling; Tan, Choo Hock; Lee, Louisa Pernee; Khor, Sook Mei; Tan, Kae Yi
Abstract: Cobra ( Naja spp.) envenoming is a life-threatening medical emergency, and a correct diagnosis is crucial to initiating timely and appropriate antivenom treatment. However, snakebite diagnostics remain unavailable in Southeast Asia. This study, therefore, developed an immunodetection assay with a potential diagnostic application for cobra envenoming. The cytotoxin of Naja kaouthia (Thai Monocled Cobra) (Nk-CTX) was purified from its venom to produce CTX-specific antibodies in rabbits and chickens. A double-antibody sandwich enzyme-linked immunosorbent assay was developed using the purified anti-Nk-CTX antibodies (immunoglobulin G and immunoglobulin Y), and its selectivity, specificity, and sensitivity for the venoms of five major cobra species in Southeast Asia ( N. kaouthia, Naja sumatrana, Naja sputatrix, Naja siamensis, and Naja philippinensis ) were studied. The results showed the immunoassay discriminates cobra venoms from other species commonly implicated in snakebites in Southeast Asia, i.e., the Malayan Krait, Many-banded Krait, King Cobra, Eastern Russell's Viper, Malayan Pit Viper and White-lipped Pit Viper. The immunoassay has a high sensitivity for the five cobra venoms, with detection limits (LoD) ranging from 0.6 to 2.6 ng/ml. Together, the findings suggest the potential diagnostic application of the cytotoxin immunoassay for cobra envenoming. The immunoassay was found to exhibit high immunoreactivity toward ten Asiatic cobra venoms (absorbance > 1.5), in contrast to African cobra venoms with low immunoreactivity (absorbance < 0.9). Considering the varying CTX antigenicity between Asiatic and African cobras, the immunoassay for African cobras should utilize antibodies produced specifically from the cytotoxins of African cobra venoms. Graphical abstract: Image 1 Highlights: Rabbit IgG and chicken IgY were raised against cytotoxin of Naja kaouthia . Cytotoxin-specific antibodies were used to develop a double-antibody sandwich immunoassay for detection of cobra venoms. Immunodetection assay provided discriminative detection for Naja kaouthia venom from non-cobra venoms. Immunodetection assay was highly immunoreactive toward venoms of 10 Asiatic cobras but weak in 11 African cobra venoms tested. Immunodetection assay of cobra cytotoxin was shown to have potential diagnostic application for cobra envenoming.